PERAN KURIKULUM PENGKADERAN IMM UIN SUNAN KALIJAGA DALAM PEMBENTUKAN KARAKTER MAHASISWA - Ahmad Bustomi (Universitas Muhammadiyah Ponorogo, 2019)
The background of this research is the existency of extra campus organizations which have an ideology contradicting with Pancasila as the Nation Ideology and its democracy system which according to researcher it strongly threatens the integrity of NKRI. On the other side, there are many news in various media which issues the confusions between Islamic Mission becoming the spirit of Islamic students organizations and the practice of some cadres in field such as fighting among islamic students and destroying campus or public fasilities. The recruitment curriculum of cadre is very important thing to be analyzed more deeply considering from where it will be seen the direction of this students’ movement working, the background and spirit of organizations. Therefore, the researcher focuses on something important to be analyzed especially related to the role of islamic student organization of extra campus on the forming of students’ character of IMM cadre in UIN Sunan Kalijaga. The selection of organization around UIN Sunan Kalijaga is chosen because of the location in Yogyakarta, in which mostly becomes a place for the establishment of student organizations and UIN Sunan Kalijaga itself has a massive organization climate.This research aims to describe the role of islamic student organization of extra campus in the forming of student characters by using a qualitative approach with the subject of research (informant) consisting of Abdul Karim and Khairunnisa. The metodes of data collection used are interview, observation, and documentation. Data analysis uses Milles Huberman model with data reduction technique, data presentation, and conclusion.The results of research show that: Firstly, The implementation of cadre curriculum IMM is as the method which has Guide in DAD called insructor amounted three people whose duty give introduction before presenter, guides the course of the class, companion fgd/fanel, looking for speakers until accountable for up to six months after the rescheduling charged by committe. The method of study which consists of lecturing, question and answer, fgd/sgd, panel, group dinamics and debate. Second, the role of curriculum shows 7 characters religious, tolerance, discipline, appreciate achievement, friendly/communicative, social care and responsible.